Ecology and systematics of the genus Liphistius (Aranae: Liphistiidae) from Peninsular Malaysia / Nurul Syuhadah Mohamed Dzarawi - Nurul Syuhadah , Mohamed Dzarawi (2016)
The primitive trap door spider genus Liphistius is currently known from few region in South East Asia, including Malaysia. In the year 2012, Malaysian Government has listed all the fourteen species and one subspecies originated from this region as protected under the Malaysian Wildlife Conservation (Amendment of Schedule) Order 2012 to protect this group from commercial collectors. Unfortunately the trap door spiders are poorly studied because of the rarity of adult’s specimens. The work on this group of conservation importance is also constrained by the difficulties in species identification. In this study the distribution of the genus Liphistius from Peninsular Malaysia was surveyed for the first time. A total of 33 population sites were investigated with new population records for several places in Terengganu, Perak, Pahang and Johor. Nine species and ten morpho species were examined in this study. All the species examined were described with information on type data, material examined and geographical distribution. The identified known species were L. malayanus, L. desultor, L. murphyorum, L. endau, L. langkawi, L. kanthan, L. batuensis, L. laruticus and L. tempurung. Images of adults, genitalia structures and distribution maps are provided. Molecular analysis was employed to help with the identification process and to clarify the species status. DNA barcoding method and neighbour joining analysis were employed to delimit the species. Bayesian inference and maximum parsimony analysis were then used to test the monophyletic and relationship of the genus Liphistius from Peninsular Malaysia. All the molecular methods conducted supported the existence of the five described species within Liphistius spp. in Peninsular Malaysia.